2nd International Conference on Wireless Intelligent and Distributed Environment for Communication WIDECOM 2019 - Woungang, Isaac; Dhurandher, Sanjay Kumar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the proceedings of the International Conference on Wireless Intelligent and Distributed Environment for Communication (WIDECOM 2019), sponsored by the University of Milan, Milan, Italy, February 11-13, 2019. The conference deals both with the important core and the specialized issues in the areas of new dependability paradigms design and performance of dependable network computing and mobile systems, as well as issues related to the security of these systems. The WIDECOM proceedings features papers addressing issues related to the design, analysis, and implementation, of infrastructures, systems, architectures, algorithms, and protocols that deal with network computing, mobile/ubiquitous systems, cloud systems, and IoT systems. It is a valuable reference for researchers, instructors, students, scientists, engineers, managers, and industry practitioners. The book's structure and content is organized in such a manner that makes it useful at a variety of learning levels. Presents the proceedings of the International Conference on Wireless Intelligent and Distributed Environment for Communication (WIDECOM 2019), Milan, Italy, February 11-13, 2019; Includes an array of topics networking computing, mobile/ubiquitous systems, cloud systems, and IoT systems; Addresses issues related to protecting information security and establishing trust in the digital space.
Chapter 1. Performance Evaluation of G.711 and GSM Codecs on VoIP Applications using OSPF and RIP Routing Protocols -- Chapter 2. Cyclic Redundancy Check based Data Authentication in Opportunistic Networks -- Chapter 3. Hybrid Cryptographic Based Approach for Privacy Preservation in Location Based Services -- Chapter 4. Design of Energy-Aware PRoPHET and Spray-and-Wait Routing Protocols for Opportunistic Networks -- Chapter 5.An Asymmetric RSA based Security Approach for Opportunistic IoT -- Chapter 6. Performance Analysis of A* Based Hop Selection Technique in Opportunistic Networks through Movement Mobility Models -- Chapter 7. Data Loss Prevention Using Document Semantic Signature -- Chapter 8. Data Loss Prevention Using Document Semantic Signature -- Chapter 9. PSARV: Particle Swarm Angular Routing in Vehicular Ad hoc Networks -- Chapter 10. A Reliable Firefly-based Routing Protocol for Efficient Communication in Vehicular Ad Hoc Networks -- Chapter 11. Exploring the Application of Random Sampling in Spectrum Sensing -- Chapter 12. White-box Cryptography: A Time-security Trade-off for the SPNbox Family -- Chapter 13. CESIS: Cost Effective and Self-regulating Irrigation System -- Chapter 14. Maximum Eigenvalue based detection using Jittered Random Sampling -- Chapter 15. Prevention of Flooding Attacks in Mobile Ad hoc Networks -- Chapter 16. Prevention of Flooding Attacks in Mobile Ad hoc Networks -- Chapter 17. Real Time Spectrum Occupancy Prediction -- Chapter 18. SCC-LBS: Secure Criss-Cross Location Based Service in Logistics.
Keywords: Telecommunication; Computer networks .; Communications Engineering, Networks; Microwaves, RF Engineering and Optical Communications; Computer Communication Networks